2016
DOI: 10.4240/wjgs.v8.i11.719
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative clinical and instrumental factors as antireflux surgery outcome predictors

Abstract: Gastroesophageal reflux disease (GERD) is nowadays a highly prevalent, chronic condition, with 10% to 30% of Western populations affected by weekly symptoms. Many patients with mild reflux symptoms are treated adequately with lifestyle modifications, dietary changes, and low-dose proton pump inhibitors (PPIs). For those with refractory GERD poorly controlled with daily PPIs, numerous treatment options exist. Fundoplication is currently the most commonly performed antireflux operation for management of GERD. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 87 publications
2
8
0
Order By: Relevance
“…Typical symptoms include heartburn and regurgitation, whereas atypical symptoms include dysphagia, bloating, chest pain, cough, and abdominal pain. 9,10 The diagnosis of GERD is typically made by corelating symptoms and objective test results. For a patient to be a candidate for LF, preoperative testing, which we advocated in our cases, include 1) upper gastrointestinal (GI) scopy, which is mandatory in all patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical symptoms include heartburn and regurgitation, whereas atypical symptoms include dysphagia, bloating, chest pain, cough, and abdominal pain. 9,10 The diagnosis of GERD is typically made by corelating symptoms and objective test results. For a patient to be a candidate for LF, preoperative testing, which we advocated in our cases, include 1) upper gastrointestinal (GI) scopy, which is mandatory in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gastroesophageal reflux is considered as a drop in esophageal pH below 5, and the number of such episodes in 24 hours is calculated for each patient and are corelated with their symptoms. [9][10][11][12] The basic goal of treatment should always be to provide symptomatic relief, prevent complications, and improve quality of life. Lifestyle modifications are considered the cornerstone of management and have proven helpful in many patients.…”
Section: Discussionmentioning
confidence: 99%
“…A 2012 retrospective study included over 2000 patients who underwent manometry and pH testing and found that patients with incompetent LES pressures had significantly higher DeMeester scores[ 70 ]. A hiatal hernia is one example of why the LES can be compromised in patients and lead to lower closing pressures[ 71 ]. The straight leg raise is another simple provocative maneuver that can be completed during HRM to assess patients with a hiatal hernia (Figure 12 ).…”
Section: Manometry and Motility Testingmentioning
confidence: 99%
“…Gastroesophageal reflux disease (GERD) is a condition which develops when the reflux of stomach contents causes troublesome symptoms and/or complications [1, 2]. The typical symptoms of GERD are heartburn and regurgitation, while the atypical symptoms of GERD include non-cardiac chest pain and extraesophageal symptoms such as chronic cough, chronic asthma, chronic laryngitis and dental erosions [35]. The prevalence of GERD in East Asia is about 2.5–7.8% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic cough defined as cough that persisits for > 8 weeks, affects 11–20% of the adult population and significantly impairs health-related quality of life [7]. GERD symptom response rates for anti-reflux surgery varies based on 1) evidence for GERD, such as ambulatory pH monitoring metrics, PPI response and GERD phenotypes, and 2) the particular symptom [3]. while laproscopic fundoplication (LF) can control typical symptoms in about 90% of patients [813], the resolution of chronic cough is less predictive (about 51–96%) [9, 10, 14, 15].…”
Section: Introductionmentioning
confidence: 99%